HUBUNGAN RESPONSE TIME DENGAN TINGKAT KEPUASAN PASIEN - Riska Indah Kumaladewi; Joko Prasetyo; Aditya Nuraminudin Aziz (Jurnal EDUNursing, 2021)
Abstract Hospital has an obligation to provide emergency services to patients, as well as to create, implement and maintain standards of emergency services in the hospital as a reference in serving patients. The patient expressed dissatisfaction about the response time in the ER to admission to the hospital ward, ineffective communication and a lack of environmental control. This review literature describes the relationship between response time and patient satisfaction. Research purposes to determine the relationship between Response Time and patient satisfaction levels. This review literature uses four databases (ProQuest, Sage, Wiley Online Library, Google Scholar) for previous studies published between 2015-2020. Some of the terms used include waiting time, satisfaction level. The PRISMA flowchart is used to summarize the article selection process. Result research: In response time conditions, emergency room officers, especially nurses, are required to be able to immediately provide fast, precise and holistic handling. Therefore, patient handling is according to priority and the role of nurses in response time can be a measure of the quality of emergency services which further provides feedback, namely the existence of patient satisfaction.Conclusion: 80% of the articles reviewed found that there was a relationship between response time and patient satisfaction.Keywords : patient satisfaction level, response time, waiting time